PENGARUH PERENCANAAN PAJAK TERHADAP KINERJA PERUSAHAAN DENGAN MANAJEMEN LABA SEBAGAI VARIABEL INTERVENING: THE EFFECT OF TAX PLANNING ON COMPANY PERFORMANCE WITH EARNINGS MANAGEMENT AS AN INTERVENING VARIABLE - Nugraheni, Titis Tatas; Wardani, Dewi Kusuma (Universitas Riau, 2023)
This study aims to examine a conceptual framework that predicts whether tax planning affects company performance through earnings management as an Intervening variable. The sample in this study is manufacturing companies of all sectors listed on the IDX in 2014-2018. The data is analyzed using Partial Least Square (PLS) with the help of smartPLS. The results of this study show the influence of variable relationships directly that tax planning has no effect on earnings management. Earnings management has no effect on the company's performance. Tax planning has no effect on the performance of the company. This study also examine variables indirectly that show results that earnings management could not mediate the effect of tax planning on the performance of the company.